Edentulous disparities among geriatric population according to the sexual difference in South Korea: a nationwide population-based study - Hyang-Ah Park; Soon-Hee Shin; Jae-In Ryu (Scientific Reports, 2023)
Abstract The proportion aged 60 years or older in the world's population is expected to double by 2050. In general, they have many complex diseases and poor oral health status. Oral health is one of the important health indicators of elderly people and it is affected by diverse factors, such as socioeconomic status. In this study, sexual difference was considered as an associated factor that is closely related to edentulism. The sexual difference might be more influential within the geriatric population because of lower economic and educational backgrounds at this stage. Edentulism was significantly higher among elderly females than males when combined with the education level. The lower the level of education, the higher the prevalence of edentulism as much as 24 ~ 28 times, especially in females (P = 0.002). These findings suggest a more complex relationship between oral health, socioeconomic status, and sexual difference.